МЕХАНИЗМ ФОРМИРОВАНИЯ АНОМАЛЬНЫХ ДЕФОРМАЦИОННЫХ ПРОЦЕССОВ В ПЕРИОД ПОДГОТОВКИ КАМЧАТСКОГО ЗЕМЛЕТРЯСЕНИЯ 2 МАРТА 1992 Г - Кузьмин Ю.О.; Чуриков В.А. (My University, 1998)
Precision leveling has been conducted during 3 years on a local profile located in a seismic fault zone, Kamchatka. The results were examined to find relations between deformation and seismicity. Superintensive vertical movements were discovered in active fault zones intersecting the leveling line in relation to the preparation of a large earthquake (M = 7,1, March 2, 1992) during the period of observation.
Keywords: 551.242;550.34